On the effect of surge protection devices (SPDs) placement for grid-connected solar PV farm - Zaini N.H.; Ab-Kadir M.Z.A.; Radzi M.A.M.; Izadi M.; Ahmad N.I.; Azis N.; Nasir M.S.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Lightning; Lightning protection; Transients; Cable length; Lightning currents; Solar PVs; Transient current; Transient voltage; Surge protection